TINJAUAN HUKUM TERHADAP PENOLAKAN NAFKAH MADHIYAH ANAK PASCA PERCERAIAN DALAM PUTUSAN PENGADILAN AGAMA TALU Nomor. 581/Pdt.G/2021/PA.Talu - Hakim, Lukmanul; Rizkal (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2025)
The primary obligation of a husband toward his wife and children is to provide financial support (nafaqah). This obligation ceases for the wife in the event of a divorce; however, it remains valid for the children. After a divorce, the husband, as the father, is still responsible for supporting his children until they reach adulthood. This principle contrasts with the decision made by the Panel of Judges at the Talu Religious Court in Decision Number 581/Pdt.G/2021/PA.Talu, in which the judges rejected the claim for madhiyah (past) child support after the divorce. This study aims to answer two main questions: What were the legal considerations of the Panel of Judges in Decision Number 581/Pdt.G/2021/PA. Talu, the ex-wife’s lawsuit against her former husband for five years of unpaid child support was rejected. This rejection is considered to lack legal justice for both the wife and the child.